On two recent geometrical characterizations of hyperellipticity - Costa, Antonio F.; Porto, Ana M. (Revista Matemática Complutense, 2004)
We obtain short and unified new proofs of two recent characterizations of hyperellipticity given in [4] and [6], as well as a way of establishing a relation between them.